2011
DOI: 10.1007/s00125-011-2378-z
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 diabetes-associated variant in TCF7L2 is associated with latent autoimmune diabetes in adult Europeans and the gene effect is modified by obesity: a meta-analysis and an individual study

Abstract: Aims/hypothesis The variants of transcription factor 7-like 2 (TCF7L2) gene have been proposed to be associated with latent autoimmune diabetes in adults (LADA). We sought to confirm the possible association in Europeans and to examine the interaction between one gene variant and clinical data. Methods The TCF7L2 rs7903146 C-to-T polymorphism was genotyped in 211 LADA, 1,297 type 2 diabetic, 545 type 1 diabetic and 1,497 control individuals from Hungary. A meta-analysis of our and previously published studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 12 publications
4
49
3
7
Order By: Relevance
“…Thus our results reiterate TCF7L2 as the most promising T2DM susceptible gene that has been most universally replicated. While the risk allele of each of the two TCF7L2 SNPs was highly significantly associated with T2DM, the greatest risk of developing the disease was conferred by rs7903146, which is consistent with the findings from other studies, such as white Europeans, West Africans, Mexicans, African Americans, Indians, and Japanese [6] [33] [34], with the exception of the study on Pima Indian populations, in which contradictory results have been reported [31].…”
Section: Discussionsupporting
confidence: 89%
“…Thus our results reiterate TCF7L2 as the most promising T2DM susceptible gene that has been most universally replicated. While the risk allele of each of the two TCF7L2 SNPs was highly significantly associated with T2DM, the greatest risk of developing the disease was conferred by rs7903146, which is consistent with the findings from other studies, such as white Europeans, West Africans, Mexicans, African Americans, Indians, and Japanese [6] [33] [34], with the exception of the study on Pima Indian populations, in which contradictory results have been reported [31].…”
Section: Discussionsupporting
confidence: 89%
“…In Europeans, the intronic TCF7L2 rs7903146 variant is the strongest identified genetic risk factor for type 2 diabetes [22]. Association has also been shown between TCF7L2 and LADA [12] in work encompassing a subset of the patients included in the current study [11]. TCF7L2 encodes a transcription factor, which is involved in maintaining the secretory function of beta cells and has been suggested to be a key determinant of beta cell mass (reviewed in [23]).…”
Section: Discussionmentioning
confidence: 77%
“…To date, consistent association has only been reported for TCF7L2 and LADA [11,12]. We hypothesised that LADA, and possibly adult-onset type 1 diabetes, is a genetic hybrid of type 1 and type 2 diabetes with increased frequency of type 2 diabetes risk genotypes.…”
Section: Introductionmentioning
confidence: 81%
“…Ez egyrészt tovább nehezíti a minor gének azonosítását, másrészt ma még jórészt ismeretlen biológiai jelentőségű gén-gén kölcsönhatásokra hívja fel a figyelmünket. Tovább bonyolítja a helyzetet, hogy miként azt munkacsoportunk is igazolta, bizonyos esetekben a béta-sejt-proliferációt és inzulinszekréciót nem autoimmun mechanizmussal befolyásoló, alapvetően 2-es típusú diabetesre hajlamosító gének (például TCF7L2) is szerepet játszhatnak az autoimmun diabetesformák patogenezisében [20].…”
Section: Minor Genetikai Faktorokunclassified